Field theory:a path integral approach - Das Ashok (World Scientific, 2006)
This unique book describes quantum field theory completely within the context of path integrals. With its utility in a variety of fields in physics, the subject matter is primarily developed within the context of quantum mechanics before going into specialized areas.
Keywords: Path integrals; Physics; Quantum field theory